About the whereabouts of indefinites - Frey, Werner (ZAS Papers in Linguistics, 2001)
The paper characterizes three different domains in the German middle field which are relevant for the interpretation of an indefinite. It is argued that the so-called 'strong' reading of an indefinite is the basic one and that the 'weak' reading needs special licensing which is mirrored by certain syntactic requirements. Some popular claims about the relation between the position and the interpretation of indefinites as well as some claims about scrambling are discussed and rejected. From the findings also follows that the strong reading of an indefinite is independent of its information status.